Estimates of combining ability and heritability in cowpea genotypes under drought stress and nonstress conditions in Uganda - Mwale, Saul Eric; Ochwo Ssemakula, Mildred; Sadik, Kassim; Alladassi, Boris; Rubaihayo, Patrick; Gibson, Paul; Singini, Wales; Edema, Richard (Journal of Plant Breeding and Crop Science, 2017)
Cowpea is an important source of food and income for small scale farmers in Uganda. Production is, however, affected by both biotic and abiotic stresses. Drought stress has recently emerged as a serious concern due to the effects of climate change. This study was therefore undertaken to estimate the general and specific combining ability effects of parents and crosses as well as estimate the heritability of delayed leaf senescence, seed yield and its components under drought stress. Five drought tolerant genotypes were crossed with four drought sensitive genotypes in a North Carolina II mating design. The study revealed that drought tolerance is conditioned by both additive and non-additive genetic effects with the predominance of non-additive genetic effects for seed yield, 100 seed weight and number of pods per plant. Delayed leaf senescence was however, controlled by additive genetic effects, implying that progenies performance could be predicted from parents General Combining Ability (GCA) effects. The cultivars SECOW 5T, IT93K-452-1 and IT98K-205-8 were good combiners for drought tolerance. The F2 families: SECOW 3B x IT98K-205-8, SECOW 5T x IT98K-205-8, SECOW 4W x IT98K- 205-8 and SECOW 1T x IT98K-205-8 had positive Specific Combining Ability(SCA) effects in seed yield, number of pods per plant and 100 seed weight, implying that they performed better than what was predicted by their parents GCA effect. As such, they are promising cross combinations that can be advanced for later generation selection.
Keywords: Drought stress; Combining ability; Water use efficiency